2D Metal–Organic Framework Nanosheets based on Pd-TCPP as Photocatalysts for Highly Improved Hydrogen Evolution - Kim, Ji Hyeon; Wu, Siming; Zdrazil, Lukas; Denisov, Nikita; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
In this report, a 2D MOF nanosheet derived Pd single-atom catalyst, denoted as Pd-MOF, was fabricated and examined for visible light photocatalytic hydrogen evolution reaction (HER). This Pd-MOF can provide a remarkable photocatalytic activity (a H2 production rate of 21.3 mmol/gh in the visible range), which outperforms recently reported Pt-MOFs (with a H2 production rate of 6.6 mmol/gh) with a similar noble metal loading. Notably, this high efficiency of Pd-MOF is not due to different chemical environment of the metal center, nor by changes in the spectral light absorption. The higher performance of the Pd-MOF in comparison to the analogue Pt-MOF is attributed to the longer lifetime of the photogenerated electron-hole pairs and higher charge transfer efficiency.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Metal–Organic Frameworks; Pd Single Atom; Photocatalysis

A Dewetted-Dealloyed Nanoporous Pt Co-Catalyst Formed on TiO2 Nanotube Arrays Leads to Strongly Enhanced Photocatalytic H-2 Production - Ji, Lei; Spanu, Davide; Denisov, Nikita; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco (Chemistry - An Asian Journal, 2020)
Pt nanoparticles are typically decorated as co-catalyst on semiconductors to enhance the photocatalytic performance. Due to the low abundance and high cost of Pt, reaching a high activity with minimized co-catalyst loadings is a key challenge in the field. We explore a dewetting-dealloying strategy to fabricate on TiO2 nanotubes nanoporous Pt nanoparticles, aiming at improving the co-catalyst mass activity for H-2 generation. For this, we sputter first Pt-Ni bi-layers of controllable thickness (nm range) on highly ordered TiO2 nanotube arrays, and then induce dewetting-alloying of the Pt-Ni bi-layers by a suitable annealing step in a reducing atmosphere: the thermal treatment causes the Pt and Ni films to agglomerate and at the same time mix with each other, forming on the TiO2 nanotube surface metal islands of a mixed PtNi composition. In a subsequent step we perform chemical dealloying of Ni that is selectively etched out from the bimetallic dewetted islands, leaving behind nanoporous Pt decorations. Under optimized conditions, the nanoporous Pt-decorated TiO2 structures show a>6 times higher photocatalytic H-2 generation activity compared to structures modified with a comparable loading of dewetted, non-porous Pt. We ascribe this beneficial effect to the nanoporous nature of the dealloyed Pt co-catalyst, which provides an increased surface-to-volume ratio and thus a more efficient electron transfer and a higher density of active sites at the co-catalyst surface for H-2 evolution.
CRIS-Team WoS Importer:2020-01-17

A facile “dark”-deposition approach for Pt single‐atom trapping on facetted anatase TiO2 nanoflakes and use in photocatalytic H2 generation - Cha, Gihoon; Mazare, Anca Valentina; Hwang, Imgon; Denisov, Nikita; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdenek; Zoppellaro, Giorgio; Tesler, Alexander; Spiecker, Erdmann; Schmuki, Patrik (Electrochimica Acta, 2022)
In recent years, single-atom (SA) catalysts have become strongly investigated in electrocatalysis and increasingly also in photocatalysis. Here we demonstrate that single-crystalline anatase TiO2 nanoflake (NF) layers after a facile thermal air annealing process provide suitable anchoring sites for Pt SAs. Remarkably, such air annealed (001) faceted single-crystalline TiO2 nanoflakes can trap and stabilize Pt SAs and assemblies when immersed into a Pt precursor solution for sufficient time in absence of any illumination, i.e., under "dark deposition” conditions. These decorated species act as more efficient co-catalysts for the H2 evolution reaction, compared to the classical Pt nanoparticles (NPs). Here we show that such single-crystal-based TiO2 photocatalyst, decorated with Pt SAs, can display a 4-fold increase in photocatalytic H2 production at a lower Pt loading than observed for a classical Pt nanoparticle Pt/TiO2 arrangement.<br
Keywords: Platinum single-atom; Photocatalysis; Hydrogen generation; Single-crystal anatase TiO2; Single-atom catalysis; “Dark”-deposition

A Few Pt Single Atoms Are Responsible for the Overall Co‐Catalytic Activity in Pt/TiO2 Photocatalytic H2 Generation - Qin, Shanshan; Denisov, Nikita; Will, Johannes; Kolarík, Jan; Spiecker, Erdmann; Schmuki, Patrik (Solar RRL, 2022)
The use of single atoms (SAs) has become a highly investigated topic in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. In the field of photocatalysis, Pt SAs on TiO2 have been reported to be a highly efficient co-catalyst in solar H2 production. Herein, the deposition of Pt SAs and nanoparticles on titania nanosheets is investigated. In particular, the Pt species responsible for the high co-catalytic activity using a cyanide leaching process is elucidated. It is shown that neither Pt0 species nor the majority of Pt SAs do significantly contribute to the co-catalytic activity of platinum on TiO2. In fact, >90% of the Pt of a standard deposition are non-active and can be removed by cyanide leaching without activity loss—as a consequence, the remaining Pt SAs amount to a remarkable turnover frequency of 4.87 × 105 h−1 for H2 evolution.<br

Critical factors for photoelectrochemical and photocatalytic H-2 evolution from gray anatase (001) nanosheets - Qin, Shanshan; Denisov, Nikita; Zhou, Xin; Zdražil, Lukáš; Fehn, Dominik; Hwang, Imgon; Bruns, Mark; Kim, Hyesung; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2022)
In recent years, the defect engineering of titania via reduction treatments has shown a high potential for enabling efficient and co-catalyst-free photocatalytic H-2 generation from methanol/water solutions. However, defect engineering simultaneously alters several properties of TiO2. Here, we use pristine (white) and hydrogenated (gray) anatase nanosheets with dominant (001) facets. By comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H-2 evolution, we show that the increased conductivity or broad visible light absorption of gray titania is not responsible for its increased activity. Instead, the true bottleneck is the hole transfer rate that is significantly accelerated while using gray instead of white modification. Moreover, the hole transfer reaction causes the accumulation of the reaction products in pure water, hindering the photocatalytic H-2 evolution over time. These combined factors explain the superior performance of gray titania over white titania in photoelectrochemical or photocatalytic water splitting.
CRIS-Team WoS Importer:2022-10-07

DC sputter deposited TiO2 layers on FTO: towards a maximum photoelectrochemical response of photoanodes - Kim, Hyesung; Wang, Yue; Denisov, Nikita; Wu, Zhenni; Kment, Stepan; Schmuki, Patrik (Journal of Materials Science, 2022)
Abstract: In this work, we examine the photoelectrochemical response of TiO2 layers prepared by reactive DC sputter deposition on conductive glass (FTO). We show that adequate conditioning of the FTO by a very thin (few nm thick) Ti interlayer and optimizing the sputter parameters, compact TiO2 anatase layers can be produced that reach incident photocurrent conversion efficiencies (IPCE) maxima peaking at 75%. This is outperforming many of the best titania photoanode structures (including high surface area 1D and 3D titania structures). The key role of the interlayer is to promote the crystallization of titania in the anatase form during the annealing process (as opposed to rutile in the interlayer-free case). Without this interlayer, an IPCE maxima of ≈43% is obtained for otherwise identically processed electrodes. The present work thus describes a most simple straightforward approach for fabricating compact, high-efficiency TiO2 (anatase) photoanodes. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-15

Effect of different hole scavengers on the photoelectrochemical properties and photocatalytic hydrogen evolution performance of pristine and Pt-decorated TiO2 nanotubes - Denisov, Nikita; Yoo, Jeong Eun; Schmuki, Patrik (Electrochimica Acta, 2019)
TiO2 nanotubes have been investigated in photoelectrochemistry and photocatalysis for more than a decade. However, up to now, a systematic investigation of different hole scavengers is still lacking. Here we investigate the effect of the most relevant sacrificial hole scavengers on the photoelectrochemical properties and photocatalytic H2 evolution performance of pristine and Pt-decorated anodic TiO2 nanotubes. We examine methanol, isopropanol, ethylene glycol, EDTA-Na2, as well as Na2SO3 and H2O2 and find that the incident photocurrent conversion efficiency (IPCE) of the TiO2 nanotubes in 0.1 M Na2SO4 electrolytes increases by 1.8–3.1 times, depending on the used hole scavenger. The efficiency increases in the sequence H2O2 < Na2SO3 < isopropanol < methanol < ethylene glycol < EDTA-Na2. In presence of any hole scavenger, for nanotubes in the length-range of 2–10 μm, the photocurrent spectra and the IPCE magnitude are independent of the tube length. The photocurrent onset potential (optical flatband potential) is significantly affected by the different type of scavengers, in line with their red-ox potential. Under open circuit conditions (photocatalytic conditions), organic hole scavengers lead to a 10.0–28.8 times higher H2 production by TiO2 nanotubes than the scavenger-free case, with a sequence MeOH > i-PrOH > EDTA-Na2 > EG, while little or even detrimental effects of Na2SO3 and H2O2 are observed (note, this inactivity is in contrast to photoelectrochemical H2 generation). These results are compared to results obtained for TiO2 particles, and discussed in terms of various concepts in the literature.
CRIS-Team Scopus Importer:2019-07-09
Keywords: H; Hole scavengers; Photocatalysis; Photoelectrochemistry; TiO

Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Establishing High Photocatalytic H-2 Evolution from Multiwalled Titanate Nanotubes - Yoo, Jeong Eun; Alshehri, Abdulmohsen Ali; Qin, Shanshan; Bawaked, Salem Mohamed; Mostafa, Mohamed Mokhtar M.; Katabathini, Narasimharao; Fehn, Dominik; Schmidt, Jochen; Mazare, Anca Valentina; Denisov, Nikita; Cha, Gi; Meyer, Karsten; et al. (ChemCatChem, 2020)
Black TiO2 in various forms has been investigated for numerous photochemical applications. In photocatalytic water splitting, "grey" titania forms have been reported to reach considerable H-2 generation rates without using a noble metal co-catalyst. Up to now, a variety of anatase powders or other morphologies has been investigated in grey and black forms. Here we describe that hydrothermal titanate/anatase nanotubes can show a strong noble metal free photocatalytic activity. For optimized "blackening" conditions, a drastically higher photocatalytic H-2 production can be obtained than for other nanoscale morphologies. This effect can further be improved with a very mild Pt doping that again shows a clearly stronger photocatalytic H-2 production than comparably loaded nanopowders.
CRIS-Team WoS Importer:2020-05-15

Facet-Control versus Co-Catalyst-Control in Photocatalytic H-2 Evolution from Anatase TiO2 Nanocrystals - Qin, Shanshan; Shui, Lancang; Osuagwu, Benedict; Denisov, Nikita; Tesler, Alexander; Schmuki, Patrik (ChemistryOpen, 2022)
Titanium dioxide (TiO2) and, in particular, its anatase polymorph, is widely studied for photocatalytic H-2 production. In the present work, we examine the importance of reactive facets of anatase crystallites on the photocatalytic H-2 evolution from aqueous methanol solutions. For this, we synthesized anatase TiO2 nanocrystals with a large amount of either 001 facets, that is, nanosheets, or 101 facets, that is, octahedral nanocubes, and examined their photocatalytic H-2 evolution and then repeated this procedure with samples where Pt co-catalyst is present on all facets. Octahedral nanocubes with abundant 101 facets produce >4 times more H-2 than nanosheets enriched in 001 facets if the reaction is carried out under co-catalyst-free conditions. For samples that carry Pt co-catalyst on both 001 and 101 facets, faceting loses entirely its significance. This demonstrates that the beneficial role of faceting, namely the introduction of 101 facets that act as electron transfer mediator is relevant only for co-catalyst-free TiO2 surfaces.
CRIS-Team WoS Importer:2022-02-11

Grätzel-Type TiO2 Anatase Layers as Host for Pt Single Atoms: Highly Efficient and Stable Photocatalytic Hydrogen Production - Kerketta, Ujjaval; Kim, Hyesung; Denisov, Nikita; Schmuki, Patrik (Advanced Energy Materials, 2023)
Single atoms (SAs) represent not only a new frontier in classic heterogeneous catalysis but are also increasingly investigated as co-catalysts in photocatalytic reactions. In contrast to classic catalysis, many photocatalytic platforms require only a very low SA loading density to reach a saturated photocatalytic activity. As a result, an optimized light harvesting/carrier transport combination in the supporting semiconductor becomes the key aspect for the overall photocatalytic efficiency. In this work, it is demonstrated that Grätzel type mesoporous TiO2 layers represent an ideal host for Pt single-atoms (SAs) that allow for a highly effective photocatalytic H2 generation. Using a layer with an optimized geometry, structure, as well as Pt SA loading, a photocatalytic H2 production is achieved of up to ≈2900 µL h−1 (under irradiation at λ = 365 nm and I = 65 mW cm−2) – a performance that is far superior to previous Pt SA/TiO2 structures based on TiO2 nanotubes, nanosheets, or metal organic frameworks. Moreover, such SA/substrate combination provides a highly stable H2 production over time. The present work thus introduces the use of this classic TiO2 nanostructure as the most effective host for Pt SAs and its use for highly efficient photocatalytic H2 production from aqueous solutions.
CRIS-Team Scopus Importer:2023-12-08
Keywords: mesoporous titanium dioxide; photocatalytic hydrogen production; Pt single atoms

Grey facet-controlled anatase nanosheets for photocatalytic H2 evolution without co-catalyst - Qin, Shanshan; Kim, Hyesung; Denisov, Nikita; Fehn, Dominik; Schmidt, Jochen; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2020)
Recently, black and grey titania in various morphologies have been intensively investigated for their high performance in photocatalytic H2 generation. Here we use titania nanosheets with a large percentage of (001) facets and hydrogenate them to activate suitable Ti3+-Ov defects for co-catalyst free H2 generation. Key to a highly active nanosheet-catalyst is the prevention of serious deformation and sintering during the thermal hydrogenation. In this work, we present a systematic investigation of different thermally treated nanosheets characterized by SEM, HR-TEM, TEM-EDX, XRD, EPR, XPS, and photocatalytic H2 evolution performance. We describe how to achieve robust grey nanosheets with an intact two-dimensional shape that can endure hydrogenation at the required high temperatures. Due to a defined faceting, these optimized "grey" nanosheets can produce photocatalytic H2 at a higher rate than previously reported best performing grey nanoparticles – this in spite of having a lower BET than the reduced nanoparticles.<br

Light‐induced agglomeration of single‐atom platinum in photocatalysis - Denisov, Nikita; Qin, Shanshan; Will, Johannes; Vasiljevic, Bojana Nedić; Skorodumova, Natalia V.; Pašti, Igor A.; Sarma, Bidyut Bikash; Osuagwu, Benedict; Yokosawa, Tadahiro; Voß, Johannes; Wirth, Janis; Spiecker, Erdmann; et al. (Advanced Materials, 2022)
With recent advances in the field of single-atoms (SAs) used in photocatalysis, an unprecedented performance of atomically dispersed co-catalysts has been achieved. However, the stability and agglomeration of SA co-catalysts on the semiconductor surface may represent a critical issue in potential applications. Here we describe the photoinduced destabilization of Pt SAs on the benchmark photocatalyst, TiO2. In aqueous solutions within illumination timescales ranging from few minutes to several hours, light-induced agglomeration of Pt SAs to ensembles (dimers, multimers) and finally nanoparticles takes place. The kinetics critically depends on the presence of sacrificial hole scavengers and the used light intensity. DFT calculations attribute the light induced destabilization of the SA Pt species to binding of surface-coordinated Pt with solution-hydrogen (adsorbed H atoms), which consequently weakens the Pt SA bonding to the TiO2 surface. Despite the gradual aggregation of Pt SAs into surface clusters and their overall reduction to metallic state, which involves >90% of Pt SAs, the overall photocatalytic H2 evolution remains virtually unaffected.<br

Light-induced In-situ Ti3+Formation in TiO2Nanosheets for Photocatalytic Hydrogen Evolution - Wierzbicka, Ewa; Osuagwu, Benedict; Denisov, Nikita; Fehn, Dominik; Meyer, Karsten; Schmuki, Patrik (IOP Conference Series: Materials Science and Engineering, 2020)
TiO2 has been the benchmark semiconductor for the production of photocatalytic H2 from aqueous media (with and without sacrificial agent). On TiO2 surfaces, the photocatalytic H2 evolution reaction in aqueous environments is kinetically severely hampered. To overcome this limitation and reach reasonable H2 generation rates, a well-elucidated approach is the use of noble metal co-catalysts. In contrast to costly noble metal approaches, it recently has been reported that titania reduction treatments can lead to a noble-metal-free photocatalytic H2 generation. So-called "grey"titania due to Ti3+ states shows intrinsically activated photocatalytic H2 evolution [1-3]. The present work demonstrates the feasibility to use in-situ photoinduced reduction to create Ti3+ states that act as intrinsic catalyst and activate hydrothermal synthetized anatase nanosheets for H2 generation to mediate the transfer of photo-induced charge carriers to the electrolyte.
CRIS-Team Scopus Importer:2020-10-23

Li+ Pre-Insertion Leads to Formation of Solid Electrolyte Interface on TiO2 Nanotubes That Enables High-Performance Anodes for Sodium Ion Batteries - Cha, Gi; Mohajernia, Shiva; Nguyen, Nhat Truong; Mazare, Anca Valentina; Denisov, Nikita; Hwang, Imgon; Schmuki, Patrik (Advanced Energy Materials, 2019)
Recently, sodium ion batteries (SIBs) have been widely investigated as one of the most promising candidates for replacing lithium ion batteries (LIBs). For SIBs or LIBs, designing a stable and uniform solid electrolyte interphase (SEI) at the electrode–electrolyte interface is the key factor to provide high capacity, long-term cycling, and high-rate performance. In this paper, it is described how a remarkably enhanced SEI layer can be obtained on TiO2 nanotube (TiO2 NTs) arrays that allows for a strongly improved performance of sodium battery systems. Key is that a Li+ pre-insertion in TiO2 NTs can condition the SEI for Na+ replacement. SIBs constructed with Li-pre-inserted NTs deliver an exceptional Na+ cycling stability (e.g., 99.9 ± 0.1% capacity retention during 250 cycles at a current rate of 50 mA g−1) and an excellent rate capability (e.g., 132 mA h g−1 at a current rate of 1 A g−1). The key factor in this outstanding performance is that Li-pre-insertion into TiO2 NTs leads not only to an enhanced electronic conductivity in the tubes, but also expands the anatase lattice for facilitated subsequent Na+ cycling.
CRIS-Team Scopus Importer:2019-12-31
Keywords: anodization; pre-lithiation; sodium ion batteries; solid electrolyte interphases; TiO

Low pH-Induced Activation of Single-Atom Pt Sites on TiO2 for Enhanced Photocatalytic H2 Evolution - Kamaleev, Maksim; Kim, Hyesung; Denisov, Nikita; Tesler, Alexander (ACS Applied Energy Materials, 2024)
The application of single atoms (SAs) has emerged as a cutting-edge approach to the cost-efficient utilization of noble metals in catalytic processes. However, the performance of SA systems under various acidity conditions has been barely investigated. Here, we use Pt SA cocatalysts anchored on thin TiO2 films as a model system, which shows a 2.3-3.2-fold enhanced H2 evolution performance at pH = 1, as compared to less acidic conditions (pH = 6 and 14, respectively), with a remarkable turnover frequency (TOF) of up to 589 #H2 site-1 s-1. Based on variations in H2 evolution performance at different pH and Pt loadings, it is clear that activation of additional Pt sites takes place in acidic conditions, which is ascribed to changes in H-binding energy. This allows better utilization of Pt SAs at high loadings and low light intensities. Despite the partial agglomeration of Pt SAs, within 4 h, a steady surface configuration of Pt sites with abundant SAs is established, which correlates with the stabilization of the H2 evolution rate. This research demonstrates a route to extend the limit of photocatalytic H2 generation with suitable SAs and reaction conditions.
CRIS-Team Scopus Importer:2024-10-25
Keywords: hydrogen evolution reaction; pH dependence; photocatalysis; single-atom cocatalysts; TiO

Magnéli Phases Doped with Pt for Photocatalytic Hydrogen Evolution - Wierzbicka, Ewa; Domaschke, Maximilian; Denisov, Nikita; Fehn, Dominik; Hwang, Imgon; Kaufmann, Marlena; Kunstmann, Babette; Schmidt, Jochen; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Applied Energy Materials, 2019)
Defined TiOx suboxides (Magnéli phases) have rarely been investigated in photocatalysis. In the current work we describe a one-step synthesis of Magnéli-containing mixed phase nanoparticles that carry directly integrated minute amounts with a few hundred ppm of Pt. Nanoparticles can act as highly effective photocatalysts, e.g., mixed phase particles of 32% anatase, 11% rutile, and 57% Magnéli phases loaded with 290 ppm of Pt which provide a 50-100 times higher H2 evolution than plain anatase loaded with a similar amount of Pt. This high photocatalytic efficiency is ascribed to a multijunction of various Magnéli titania species and Pt.
CRIS-Team Scopus Importer:2019-12-20
Keywords: H; Magnéli phase; multiphase titania; photocatalysis; Pt cocatalyst

Minuscule Amounts of Pt Single Atoms Selectively Loaded on Minor (101) Facet of Anatase Crystallites Enables Outstanding Utilization Efficiency for Photocatalytic H2 Production - Qin, Shanshan; Denisov, Nikita; Osuagwu, Benedict; Kolařík, Jan; Sarma, Bidyut Bikash; Baďura, Zdeněk; Schmuki, Patrik (Advanced Functional Materials, 2025)
Pt single atoms (SAs) on TiO2 have been identified as effective co-catalysts in solar photocatalytic H2 production. In this study, Pt SAs is deposited on single crystal anatase nanosheets (NSs) with minor (101) and major (001) facets and expose them to various thermal treatments in air, Ar, and Ar-H2 environments. It is found that through Ar-H2 annealing Pt-species can be accumulated exclusively on the minor (101) facets, i.e., they can be concentrated selectively on the facet where electron exit occurs. This optimally establishes a high photocatalytic H2 evolution efficiency for an extremely low overall Pt SA loading of ≈0.005 wt.% on the anatase crystallites. For this most active SA placement, 11.7 mmol g−1 h−1 H2 production is obtained with a turnover frequency (TOF) up to 253 #H2 site−1 s−1. Note that the corresponding Pt SAs density of 3.1 × 104 atoms µm−2 is established by loading from only 0.2 µm Pt solution. These findings demonstrate that placing a very low density of Pt SAs as an electron transfer co-catalyst onto the electron exit sites of a light-harvesting structure (i.e., there where it is needed) can provide a most active photocatalytic structure with an outstanding Pt utilization.
CRIS-Team Scopus Importer:2025-02-14
Keywords: hydrogen evolution; photocatalysis; platinum; single-atom catalysts; TiO

Photocatalytic H2 Generation: Controlled and Optimized Dispersion of Single Atom Co-Catalysts Based on Pt-TCPP Planar Adsorption on TiO2 - Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
When using single atoms (SAs) as a co-catalyst in photocatalytic H2 generation, achieving a well-dispersed, evenly distributed and adjustable SA surface density on a semiconductor surface is a challenging task. In the present work we use the planar adsorption of tetrakis-(4-carboxyphenyl)-porphyrin (TCPP) and its platinum coordinated analogue, Pt-TCPP, onto anatase TiO2 surfaces to establish a spatially controlled decoration of SAs. We show that the surface Pt SA density can be very well controlled by co-adsorption of Pt-TCPP and TCPP in the planar monolayer regime, and by adjusting the Pt-TCPP to TCPP ratio a desired well dispersed surface density of SAs up to 2.6×105 atoms μm−2 can be established (which is the most effective Pt SA loading for photocatalysis). This distribution and the SA state are maintained after a thermal treatment in air, and an optimized SA density as well as a most active form of Pt for photocatalytic H2 evolution can be established and maintained.
CRIS-Team Scopus Importer:2024-02-16
Keywords: hydrogen evolution; photocatalysis; platinum; porphyrins; single-atom catalysts

Photocatalytic Synthesis of Oxidized Graphite Enabled by Grey TiO2 and Direct Formation of a Visible-Light-Active Titania/Graphene Oxide Nanocomposite - Nasir, Amara; Mazare, Anca Valentina; Zhou, Xin; Qin, Shanshan; Denisov, Nikita; Zdrazil, Lukas; Kment, Stepan; Zboril, Radek; Yasin, Tariq; Schmuki, Patrik (Chemphotochem, 2022)
Herein we report a one-step, low cost, photocatalytic method for the synthesis of graphene oxide (GO) from commercial graphite using grey TiO2 as a photocatalyst. GO formation is achieved by UV-illumination of a slurry of well-dispersed grey TiO2 and commercial graphite. Light-induced valence-band holes from grey TiO2 then lead to an oxidation and exfoliation of graphite, resulting in the formation of visible-light-active GO. An optimal level of graphite oxidation can be established by controlling the UV illumination time. Moreover, the resulting GO-decorated TiO2 is directly active as a visible-light-active photocatalyst that can, for example, be used for pollution degradation.
CRIS-Team Scopus Importer:2022-04-15
Keywords: graphene oxide; graphite; grey TiO; methylene-blue degradation; UV illumination

Photocurrent conversion efficiency of TiO2 nanotube photoanodes in dependence of illumination intensity - Denisov, Nikita; Zhou, Xin; Cha, Gi; Schmuki, Patrik (Electrochimica Acta, 2021)
In the present work, we investigate the photoresponse of TiO2 nanotube photoanodes as a function of the illumination intensity and compare it to compact anodic TiO2 layers. While for the compact layers, in line with expectations, the IPCE is virtually independent of the light intensity, we find for the nanotube morphology a significant increase in the magnitude of the IPCE with lowering the illumination intensity. Moreover, for low light intensities a noticeable change in the IPCE spectra, a substantial slowdown of the transient photocurrent kinetics, an increase of the charge transport time constants, and an anodic shift of the optical flat-band potential is observed. We attribute the sensitivity of the IPCE and other photoresponse effects mainly to a hole accumulation and trapping caused by higher illumination intensities – this effect is particularly strong due to the geometry of the tubes. The observed effects have significant implications for the interpretation and comparability of the TiO2 NT photocurrent data.
CRIS-Team Scopus Importer:2021-03-19
Keywords: IMPS; IPCE; Mott-Schottky analysis; Photoelectrochemistry; TiO2 nanotubes

Photoelectrochemical performance of facet-controlled TiO2nanosheets grown hydrothermally on FTO - Shahvardanfard, Fahimeh; Cha, Gi; Denisov, Nikita; Osuagwu, Benedict; Schmuki, Patrik (Nanoscale Advances, 2021)
Single crystal anatase TiO2nanosheets (TiO2-NSs) are grown hydrothermally on fluorine-doped tin oxide (FTO). By systematically changing the hydrothermal conditions such as reaction time, initial concentration of Ti precursor, F precursor, and HCl as an additive, a wide variety of TiO2-NSs, with different morphologies and faceting have been synthesized. For the different morphologies and different facet ratios (anataseS001/S001+101), the photoelectrochemical response is characterized and compared. We find that for photoanodes in neutral electrolytes, the magnitude of the photocurrent depends strongly on the growth parameters, that is, peak IPCEs can vary from 11.7% to 61%. For a wide range of parameters, the key parameter deciding on the photocurrent is the effective electrochemically active area of the electrode. Only for very high facet ratios >91%, the photoresponse can be strongly influenced by faceting - for samples with aS001/S001+101of 91%, IPCE value of ≈84% is obtained. This work defines not only optimized synthesis conditions for a most effective growth of these single crystalline electrode, but also represents fundamental data for further applications of such electrodes.
CRIS-Team Scopus Importer:2021-02-26

Photoelectrochemical performance of TiO2 photoanodes: Nanotube versus nanoflake electrodes - Zhou, Xin; Denisov, Nikita; Cha, Gi; Hwang, Imgon; Schmuki, Patrik (Electrochemistry Communications, 2021)
In the present work, we compare the photoresponse of vertically erected (VE) single crystal anatase layers with that of widely used TiO2 nanotube layers. These VE-anatase layers were grown hydrothermally, directly on fluorine-doped tin oxide (FTO) glass, and consist of an array of anatase single crystal flakes with preferred (0 0 1) facets. As formed, these single crystal layers are fluorine terminated – this termination can be removed by a thermal treatment in air. We compare the photocurrent magnitude and photocurrent transients using intensity-modulated photocurrent spectroscopy (IMPS). We find that the “de-fluorinated” VE-anatase layers show significantly higher photocurrents than the comparable nanotube layers. This high efficiency of the VE-anatase layers is due to the electron transport being 100 times faster in these single crystal electrodes, provided that the blocking fluorine termination is removed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IMPS; IPCE; Photocurrent transients; TiO; VE-anatase layers

Photoelectrochemical properties of “increasingly dark” TiO2 nanotube arrays - Denisov, Nikita; Qin, Shanshan; Cha, Gi; Yoo, Jeong Eun; Schmuki, Patrik (Journal of Electroanalytical Chemistry, 2020)
“Black” TiO2 nanotube arrays (TNTAs) of different darkness are formed by thermal reduction of anodic TiO2 nanotube layers in H2 atmosphere at different temperatures (300–500 °C), and their (photo-)electrochemical properties are studied by IPCE spectroscopy, transient photocurrent measurements, IMPS, PEIS, CV, and Mott-Schottky analysis. Hydrogenation of the TNTAs leads to the enhancement of their IPCE (by up to 1.5 times), despite increased recombination losses at anodic potentials. Reduced TNTAs demonstrate a “metallic” behavior by a characteristic frequency response of their impedance and phase angle, reduced charge transfer resistance at anodic bias, increased double layer capacitance, and remarkably increased donor densities (up to 7.25 × 1023 cm−3). The observed alterations in the properties of TNTAs after hydrogenation are ascribed to the formation of defects and TiHx.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Anodization; Black titania; Hydrogenation; Nanotubes; Photoelectrochemistry; TiO

Providing significantly enhanced photocatalytic H2 generation using porous PtPdAg alloy nanoparticles on spaced TiO2 nanotubes - Nguyen, Nhat Truong; Ozkan, S.; Hejazi, Seyedsina; Denisov, Nikita; Tomanec, Ondrej; Zboril, R.; Schmuki, Patrik (International Journal of Hydrogen Energy, 2019)
In the present work we introduce a simple approach to produce porous PtPdAg alloy nanoparticles on TiO2 nanotubes by a simple combined sputtering-dewetting-dealloying process. In a first step, three individual metals (Pt, Pd and Ag) were sequentially sputter-deposited on spaced TiO2 nanotubes, followed by a thermal dewetting treatment in Ar to convert these metal layers into ternary PtPdAg alloyed particles. Dealloying was carried out by a selective chemical dissolution of Ag in piranha solution that finally generated porous alloyed nanoparticles located on the TiO2 nanotube walls. The porous PtPdAg-decorated TiO2 nanotubes show enhanced photocatalytic H2 generation in comparison with porous Pt (67% increase) or any monometallic decoration (>120% increase). The photocatalytic enhancement is not only due to the increased number of active sites (larger surface area) of the porous particles but also due to the synergistic effects of the different alloying elements.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Dealloying; Dewetting; Photocatalytic H; PtPd alloy; TiO

Pt-single atom decorated TiO2: Tuning anodic TiO2 nanotube structure and geometry toward a high-performance photocatalytic H2 production - Chen, Xuewen; Qin, Shanshan; Denisov, Nikita; Kure-Chu, Song Zhu; Schmuki, Patrik (Electrochimica Acta, 2023)
Atomically dispersed Pt single atoms (SAs) on titania have been reported to be a highly effective co-catalyst in photocatalytic H2 generation. In this report, we grew layers of anodic TiO2 nanotubes (NTs) varying the lengths of the NTs from 1 to 18 μm as well as their crystalline state by thermal annealing over a wide range of temperatures (350 °C – 800 °C). We then decorated the nanotubes with single atom (SA) Pt co-catalysts deposited from H2PtCl6 solutions with various concentrations of 0.001–2 mM Pt and evaluate the photocatalytic H2 generation performance for the different NT layers under UV and solar illumination. The highest photocatalytic performance is achieved for 15–18 μm long anatase NTs decorated with Pt SAs from a 0.01 mM H2PtCl6 solution (leading to a Pt SA surface concentration of 5.6 × 105 /µm2). Except for a sufficient SA Pt loading and an anatase structure, the key parameter is the photon absorption length for near-band-gap UV and AM 1.5 light. Such optimized Pt SA@TiO2 NTs show a most efficient H2, outperforming many other photocatalytic 3D titania structures, such as titania-based powders, flakes, and Metal–Organic Frameworks (MOFs) tested under the same illumination conditions.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Photocatalytic H; Pt single atoms; TiO; TiO; TiO

Pt single atoms dispersed in a hybrid MOFox-in-nanotube structure for efficient and long-term stable photocatalytic H2 generation - Qin, Shanshan; Guo, Junli; Chen, Xuewen; Cao, Ran; Denisov, Nikita; Song, Yan Yan; Schmuki, Patrik (Journal of Materials Chemistry A, 2023)
Atomically dispersed Pt single atoms (SAs) have been reported to be a highly effective co-catalyst on TiO2 for photocatalytic H2 generation. Many TiO2 supports have been explored for hosting Pt SAs. Particularly 1D titania hosts allow for an optimized light and charge carrier management. But, attached Pt SAs often suffer from agglomeration during the photocatalytic process. In this context, titania-based metal-organic frameworks (MOFs), such as MIL-125, have attracted wide attention, as they provide stable anchoring sites for Pt SAs. To combine the beneficial features of the 1D TiO2 morphology with the SA stability, we introduce here a hierarchical structure, where the Pt SAs are dispersed in MOF-derived porous oxide features that are embedded in aligned anodic TiO2 nanotubes. This hybrid structure is intrinsically (within the nanotubes) synthesized and combines the excellent light harvesting and carrier transport properties of titania nanotubes with the beneficial features of MOF. As a result of this synergy, we obtain not only a high photocatalytic H2 evolution efficiency but most importantly a remarkably long-term stability of H2 evolution under UV light (365 nm) or simulated solar light (AM 1.5).
CRIS-Team Scopus Importer:2023-09-15

Pt Single Atoms Loaded on Thin-Layer TiO2 Electrodes: Electrochemical and Photocatalytic Features - Zhou, Xin; Wang, Yue; Denisov, Nikita; Kim, Hyesung; Kim, Ji Hyeon; Will, Johannes; Spiecker, Erdmann; Vaskevich, Alexander; Schmuki, Patrik (Small, 2024)
Recently, the use of Pt in the form of single atoms (SA) has attracted considerable attention to promote the cathodic hydrogen production reaction from water in electrochemical or photocatalytic settings. First, produce suitable electrodes by Pt SA deposition on Direct current (DC)-sputter deposited titania (TiO2) layers on graphene—these electrodes allow to characterization of the electrochemical properties of Pt single atoms and their investigation in high-resolution HAADF-STEM. For Pt SAs loaded on TiO2, electrochemical H2 evolution shows only a very small overpotential. Concurrent with the onset of H2 evolution, agglomeration of the Pt SAs to clusters or nanoparticles (NPs) occurs. Potential cycling can be used to control SA agglomeration to variable-size NPs. The electrochemical activity of the electrode is directly related to the SA surface density (up to reaching the activity level of a plain Pt sheet). In contrast, for photocatalytic H2 generation already a minimum SA density is sufficient to reach control by photogenerated charge carriers. In electrochemical and photocatalytic approaches a typical TOF of ≈100–150 H2 molecules per second per site can be reached. Overall, the work illustrates a straightforward approach for reliable electrochemical and photoelectrochemical investigations of SAs and discusses the extraction of critical electrochemical factors of Pt SAs on titania electrodes.
CRIS-Team Scopus Importer:2024-08-23
Keywords: anatase thin film electrode; electrocatalytic hydrogen evolution; graphene; photocatalytic hydrogen evolution; Pt Single atom

Pt Single Atoms on TiO2 Can Catalyze Water Oxidation in Photoelectrochemical Experiments - Wu, Siming; Wu, Lu; Denisov, Nikita; Badura, Zdenek; Zoppellaro, Giorgio; Yang, Xiao Yu; Schmuki, Patrik (Journal of the American Chemical Society, 2024)
Photoelectrochemical water splitting on n-type semiconductors is highly dependent on catalysis of the rate-determining reaction of O2 evolution. Conventionally, in electrochemistry and photoelectrochemistry O2 evolution is catalyzed by metal oxide catalysts like IrO2 and RuO2, whereas noble metals such as Pt are considered unsuitable for this purpose. However, our study finds that Pt, in its single-atom form, exhibits exceptional cocatalytic properties for photoelectrochemical water oxidation on a TiO2 photoanode, in contrast to Pt in a nanoparticle form. The decoration of Pt single atoms onto TiO2 yields a remarkable current density of 5.89 mA cm-2 at 1.23 VRHE, surpassing bare TiO2 (or Pt nanoparticle decorated TiO2) by 2.52 times. Notably, this enhancement remains consistent over a wide pH range. By accompanying theoretical work, we assign this significant enhancement to an improved charge transfer and separation efficiency along with accelerated kinetics in the oxygen evolution reaction facilitated by the presence of Pt single atoms on the TiO2 surface.
CRIS-Team Scopus Importer:2024-06-21

Pt Single Atoms on TiO2 Polymorphs-Minimum Loading with a Maximized Photocatalytic Efficiency - Qin, Shanshan; Denisov, Nikita; Sarma, Bidyut Bikash; Hwang, Imgon; Doronkin, Dmitry E.; Tomanec, Ondrej; Kment, Stepan; Schmuki, Patrik (Advanced Materials Interfaces, 2022)
For more than 20 years, Pt/TiO2 represents the benchmark photocatalyst/co-catalyst platform for photocatalytic hydrogen (H-2) generation. Here, single atom (SA) Pt is decorated on different polymorphs of TiO2 (anatase, rutile, and the mixed phase of P25) using a simple immersion anchoring approach. On P25 and anatase, Pt SAs act as highly effective co-catalyst for pure water splitting with a photocatalytic H-2 evolution activity (4600 mu mol h(-1) g(-1))-on both polymorphs, SA deposition yields a significantly more active photocatalyst than those decorated with classic Pt nanoparticles or conventional SA deposition approaches. On rutile, Pt SAs provide hardly any co-catalytic effect. Most remarkable, for P25, the loading of Pt SAs from precursor solution with a very low concentration (<1 ppm Pt) leads already to a maximized co-catalytic effect. This optimized efficiency is obtained at 5.3 x 10(5) atoms mu m(-2) (at macroscopic loading of 0.06 at%)-for a higher concentration of Pt (a higher density of SAs), the co-catalytic efficiency is significantly reduced due to H-2/O-2 recombination. The interactions of the SA Pt with the different polymorphs that lead to this high co-catalytic activity of SA Pt at such low concentrations are further discussed.
CRIS-Team WoS Importer:2022-07-08
Keywords: diffuse reflectance infra-red spectroscopy; photocatalytic H 2 evolution photoluminescence; Pt single atoms; TiO 2 polymorphs; X-ray absorption fine structure; X-ray absorption near-edge spectra

Reactive Deposition Versus Strong Electrostatic Adsorption (SEA): A Key to Highly Active Single Atom Co-Catalysts in Photocatalytic H2 Generation - Wang, Yue; Qin, Shanshan; Denisov, Nikita; Kim, Hyesung; Bad'ura, Zdeněk; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced Materials, 2023)
In recent years, the use of single atoms (SAs) has become of a rapidly increasing significance in photocatalytic H2 generation; here SA noble metals (mainly Pt SAs) can act as highly effective co-catalysts. The classic strategy to decorate oxide semiconductor surfaces with maximally dispersed SAs relies on “strong electrostatic adsorption” (SEA) of suitable noble metal complexes. In the case of TiO2 – the classic benchmark photocatalyst – SEA calls for adsorption of cationic Pt complexes such as [(NH3)4Pt]2+ which then are thermally reacted to surface-bound SAs. While SEA is widely used in literature, in the present work it is shown by a direct comparison that reactive attachment based on the reductive anchoring of SAs, e.g., from hexachloroplatinic(IV) acid (H2PtCl6) leads directly to SAs in a configuration with a significantly higher specific activity than SAs deposited with SEA – and this at a significantly lower Pt loading and without any thermal post-deposition treatments. Overall, the work demonstrates that the reactive deposition strategy is superior to the classic SEA concept as it provides a direct electronically well-connected SA-anchoring and thus leads to highly active single-atom sites in photocatalysis.
CRIS-Team Scopus Importer:2023-08-18
Keywords: highly reactive single-atom deposition; photocatalytic H; Pt co-catalysts; sputtered anatase layers

Self-assembly of a Ni(I)-photocatalyst for plain water splitting without sacrificial agents - Qin, Shanshan; Badura, Zdenek; Denisov, Nikita; Tomanec, Ondrej; Mohajernia, Shiva; Liu, Ning; Kment, Stepan; Zoppellaro, Giorgio; Schmuki, Patrik (Electrochemistry Communications, 2021)
The present work describes a self-assembling photocatalytic system that is observed when illuminating grey titania nanoparticles in suspension with a plain aqueous Ni2+ solution. Such a suspension (in contrast to white titania), under UV illumination, increasingly produces H2 from neutral water. We show that the origin of this self-activation is not the light-induced deposition of Ni0 or another Ni-catalyst compound on the titania surface. Rather, in-situ electron paramagnetic resonance (EPR) clearly indicates that the activation is due to a light-induced formation of a suitable defect structure (Ti3+-OV) on grey titania, combined with the formation of an intermediate monovalent nickel (Ni(I)) electron transfer relay. Remarkably, the resulting Ni+/TiO2/Ti3+ photocatalyst operates in absence of any noble metal or sacrificial agent.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Hydrogen evolution; Hydrogenated anatase titania; Ni(I)-photocatalyst; Plain water splitting; Self-assembly

Self‐Enhancing H2 Evolution from TiO2 Nanostructures under Illumination - Wierzbicka, Ewa; Zhou, Xuemei; Denisov, Nikita; Yoo, Jeong Eun; Fehn, Dominik; Liu, Ning; Meyer, Karsten; Schmuki, Patrik (Chemsuschem, 2019)
Illumination of anatase in an aqueous methanolic solution leads to the formation of Ti 3+ sites that are catalytically active for the generation of dihydrogen (H 2 ). With increasing illumination time, a light-induced self-amplification of the photocatalytic H 2 production rate can be observed. The effect is characterized by electron paramagnetic resonance (EPR) spectroscopy, reflectivity, and photoelectrochemical techniques. Combined measurements of H 2 generation rates and in situ EPR spectroscopic observation over the illumination time with AM 1.5G or UV light establish that the activation is accompanied by the formation of Ti 3+ states, which is validated through their characteristic EPR resonance at g=1.93. This self-activation and amplification behavior can be observed for anatase nanoparticles and nanotubes.
CRIS-Team Scopus Importer:2019-05-02
Keywords: defects; hydrogen evolution; nanomaterials; photocatalysis; titania

Single-Atom Catalysts on C3N4: Minimizing Single Atom Pt Loading for Maximized Photocatalytic Hydrogen Production Efficiency - Lazaar, Nawres; Wu, Siming; Qin, Shanshan; Hamrouni, Abdessalem; Bikash Sarma, Bidyut; Doronkin, Dimitry E.; Denisov, Nikita; Lachheb, Hinda; Schmuki, Patrik (Angewandte Chemie International Edition, 2025)
The use of metal single atoms (SAs) as co-catalysts on semiconductors has emerged as a promising technology to enhance their photocatalytic hydrogen production performance. In this study, we describe the deposition of very low amounts of Pt SAs (<0.1 at %) on exfoliated graphitic carbon nitride (C3N4) by a direct Pt−deposition approach from highly dilute chloroplatinic acid precursors. We find that − using this technique−a remarkably low loading of highly dispersed Pt SAs (0.03 wt %) on C3N4 is sufficient to achieve a drastic decrease in the overall charge transfer resistance and a maximized photocatalytic efficiency. The resulting low-loaded Pt SAs/C3N4 provides a H2 production rate of 1.66 m mol/h/mg Pt, with a remarkable stability against agglomeration; even during prolonged photocatalytic reactions no sign of light-induced Pt agglomerations can be observed. We ascribe the high performance and stability to the site-selective, stable coordination of Pt within the C3N4 structure. Notably the H2 production rate of the low-loaded Pt SAs surpasses the activity of Pt SAs deposited by other techniques or nanoparticles at comparable or even higher loading – the optimized Pt SAs decorated C3N4 show ≈5.9 times higher rate than Pt NP decorated C3N4.
CRIS-Team Scopus Importer:2025-01-31
Keywords: C; dark deposition; H; photocatalysis; Pt single atoms

Single Atoms in Photocatalysis: Low Loading Is Good Enough! - Qin, Shanshan; Will, Johannes; Kim, Hyesung; Denisov, Nikita; Carl, Simon; Spiecker, Erdmann; Schmuki, Patrik (ACS Energy Letters, 2023)
We disperse Pt single atoms (SAs) with different loading densities on anatase TiO2 thin films and evaluate the photocatalytic H2 generation as a function of the incident light intensity. We show that under common illumination intensities (such as terrestrial solar illumination), a minuscule Pt SA loading of ∼105 atoms μm-2 (surface Pt content ∼0.1 at.%) is sufficient to achieve a maximized H2 production rate. This results in a maximum turnover frequency at a single Pt atom site of ∼300 H2 molecules s-1. For a vast majority of illumination conditions and a suitable surface configuration, it is not the density of co-catalytic sites that is rate-determining (a high loading is not needed!), but the charge carrier generation (and flux of photoelectrons to the co-catalytic centers) determines the overall reaction rate. This is in stark contrast to SA catalysis of classic chemical reactions where generally a maximum loading of reactive SA delivers a maximum activity.
CRIS-Team Scopus Importer:2023-02-10

Stable and Highly Active Single Atom Configurations for Photocatalytic H2 Generation - Wang, Yue; Denisov, Nikita; Qin, Shanshan; Gonçalves, Danielle Santos; Kim, Hyesung; Sarma, Bidyut Bikash; Schmuki, Patrik (Advanced Materials, 2024)
The employment of single atoms (SAs), especially Pt SAs, as co-catalysts in photocatalytic H2 generation has gained significant attention due to their exceptional efficiency. However, a major challenge in their application is the light-induced agglomeration of these SAs into less active nanosized particles under photocatalytic conditions. This study addresses the stability and reactivity of Pt SAs on TiO2 surfaces by investigating various post-deposition annealing treatments in air, Ar, and Ar-H2 environments at different temperatures. It is described that annealing in an Ar-H2 atmosphere optimally stabilizes SA configurations, forming stable 2D rafts of assembled SAs ≈0.5–1 nm in diameter. These rafts not only resist light-induced agglomeration but also exhibit significantly enhanced H2 production efficiency. The findings reveal a promising approach to maintaining the high reactivity of Pt SAs while overcoming the critical challenge of their stability under photocatalytic conditions.
CRIS-Team Scopus Importer:2024-04-12
Keywords: photocatalytic H; Pt co-catalyst; single atom configurations; sputtered anatase layers

Thermally-induced agglomeration tailors the stability of Pt SAs on TiO2 and use in photocatalytic H2 generation - Will, Johannes; Denisov, Nikita; Qin, Shanshan; Wu, Mingjian; Wang, Yue; Kim, Hyesung; Karpstein, Nicolas; Dierner, Martin; Schmuki, Patrik; Spiecker, Erdmann (Journal of Materials Chemistry A, 2025)
Thermally-induced agglomeration of Pt single atoms (SAs) on anatase TiO2 thin films is exploited for tuning their activity in photocatalytic H2 generation. After thermal treatment at temperatures ranging from 350 to 650 °C in an Ar atmosphere, a more than fivefold higher photocatalytic activity is achieved under optimized conditions. The Pt species obtained after annealing at different temperatures are monitored via ex situ and in situ transmission electron microscopy. For in situ measurements, a gas cell system operating at 700 mbar is utilized. Structural data obtained in the temperature range from 250 to 950 °C demonstrate the co-existence of SA species and agglomerates over the whole temperature range, and give fundamental insights into thermal and light-induced agglomeration processes, including nucleation, growth and ripening of Pt species on TiO2. Under optimized annealing conditions Pt is present as a mixture of SAs, 2D rafts and nanoparticles. Data show that annealing can stabilize the Pt species against light-induced agglomeration and detailed analysis reveals such SAs (realized under optimized annealing conditions) provide the most active sites (in comparison with various agglomerates). We further emphasize the importance of conducting atomic-scale structural characterization both before and after photocatalysis to accurately establish the process-structure-property-performance relationships of SAs in photocatalysis.
CRIS-Team Scopus Importer:2025-04-11

Thermal Ramping Rate during Annealing of TiO2 Nanotubes Greatly Affects Performance of Photoanodes - Raza, Waseem; Hwang, Imgon; Denisov, Nikita; Schmuki, Patrik (physica status solidi (a), 2021)
Herein, highly ordered TiO2 nanotube (NT) arrays on a Ti substrate is synthesized in a fluoride-containing electrolyte, using the electrochemical anodization method, which yields amorphous oxide tubes. The effects of different thermal annealing profiles for the crystallization of the amorphous TiO2 NTs are studied. It is found that the temperature ramping rate has a significant impact on the magnitude of the resulting photocurrents (incident photon-to-current conversion efficiency [IPCE]) from the tubes. No appreciable changes are observed in the crystal structure and morphology of the TiO2 NTs for different annealing profiles (to a constant temperature of 450 °C). The electrochemical properties of the annealed TiO2 NTs are investigated using intensity-modulated photocurrent spectroscopy (IMPS), open-circuit potential decay, and Mott–Schottky analysis. The results clearly show that the annealing ramping rate of 1 °C s−1 leads to the highest IPCE performance. This beneficial effect can be ascribed to a most effective charge separation and electron transport (indicating the least amount of trapping states in the tubes). Therefore, the results suggest that controlling the annealing ramping rate is not only a key factor affecting the defect structure but also a powerful tool to tailor the physical properties, and photocurrent activity of TiO2 NTs.
CRIS-Team Scopus Importer:2021-05-07
Keywords: electrochemical anodization; photoanodes; photoelectrochemistry; ramping rates; TiO

Water Annealing of TiO2 Nanotubes for Photocatalysis Revisited - Fu, Fan; Cha, Gi; Denisov, Nikita; Chen, Yuyue; Zhang, Yan; Schmuki, Patrik (ChemElectroChem, 2020)
Over the past years, so-called water annealing of TiO2 nanotube (NT) arrays has attracted considerable attention as a tool to enhance the nanotubes’ photocatalytic properties. The present work investigates the effect of different water-annealing treatments on TiO2 nanotubes and compares it to thermally annealed tubes. We find that the most effective water annealing is water immersion of TiO2 NT arrays at 70 °C for several days. The two main effects are i) a partial crystallization of the tubes to anatase, and ii) an etching of the tube walls that leads to a roughening of the walls and, thus, to a higher surface area. Under the best conditions, water annealing is almost as effective in providing enhanced photocatalytic AO7 degradation as a classic thermal annealing of the tubes. We, however, find that water annealed tubes – due to their only partial crystallization – do not perform well when used as photoelectrodes. For photocatalysis, most efficient is a combination of water annealing, followed by thermal annealing, which provides both a larger surface area and a high crystallinity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: anodization; crystallinity; photocatalytic reaction; TiO; water annealing